Work, Jobs and Well-Being across the Millennium - Clark, Andrew E.. (OECD Publishing, 2009)
This paper uses repeated cross-section data ISSP data from 1989, 1997 and 2005 to consider movements in job quality. It is first underlined that not having a job when you want one is a major source of low well-being. Second, job values have remained fairly stable over time, although workers seem to give increasing importance to the more "social" aspects of jobs: useful and helpful jobs. The central finding of the paper is that, following a substantial fall between 1989 and 1997, subjective measures of job quality have mostly bounced back between 1997 and 2005. Overall job satisfaction is higher in 2005 than it was in 1989. Last, the rate of self-employment has been falling gently in ISSP data; even so three to four times as many people say they would prefer to be self-employed than are actually self-employed. As the self-employed are more satisfied than are employees, one consistent interpretation of the above is that the barriers to self-employment have grown in recent years
Keywords: Social Issues/Migration/Health